It's a Kiki!: Developmental benefits of the Kiki scene for Black gay/bisexual/transgender adolescents/emerging adults. Issue 1 (2nd January 2022) - Harper, Gary W.; LaBoy, Richard; Castillo, Marne; Johnson, Gabriel L.; Hosek, Sybil G.; Jadwin-Cakmak, Laura
Abstract: Younger members of the House and Ball Community (HBC) have created an emerging social scene called "Kiki" that has shared elements with the HBC. Given the growing popularity of the Kiki scene in urban communities with large numbers of Black gay, bisexual, and transgender (GBT) adolescents and emerging adults, it is important to understand the developmental benefits of the Kiki scene. We conducted individual in-depth interviews with 30 GBT adolescents and emerging adults (ages 15-24) who attended Kiki-related events and 15 older opinion leaders affiliated with the HBC. Participants described how the Kiki scene provides them with a range of supportive and affirming functions and offers a place where they can achieve important developmental milestones. The results clustered into three primary thematic areas of development: Executive Functioning Development, Social-Emotional Development, and Physical and Emotional Safety during Development. Within each of these thematic areas are sub-themes that further explicate the ways in which these functions are supported. We believe this to be one of the first papers exclusively focused on the positive aspects of the Kiki scene for adolescent and emerging adult development, and we encourage other researchers to further explore this emerging socializing force and its potential benefits to development.